2003
DOI: 10.1159/000074305
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A Promotes IL-4 Production by Th2 Cells

Abstract: Background: It has been proposed that estrogen plays an important role in modulating the Th1/Th2 cytokine balance. From this viewpoint, chemicals with estrogenic responses were expected to possess similar immunoregulatory roles which have not been defined to date. To address this, we studied the effects of one of the estrogenic chemicals, bisphenol A (BPA), on the in vitro production of Th1 and Th2 cytokines. Methods: Mesenteric lymph node cells from Trichinella spiralis (Ts)-infected mice were incubated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 33 publications
3
27
0
Order By: Relevance
“…(intra peritoneal) administration of BPA. Tian 21) reported that Th2-type cytokine production by mesenteric lymph node cells increased markedly in Trichinella spiralis-infected mice inoculated orally with BPA. Our results indicate that the inhibitory effect of BPA on cytokine secretion was more effective on IL-4 than IFN-, and that therefore the immune responses developed a tendency to a Th1-type reaction, although the effects were not very strong (Fig.…”
Section: Ova (µM)mentioning
confidence: 99%
See 1 more Smart Citation
“…(intra peritoneal) administration of BPA. Tian 21) reported that Th2-type cytokine production by mesenteric lymph node cells increased markedly in Trichinella spiralis-infected mice inoculated orally with BPA. Our results indicate that the inhibitory effect of BPA on cytokine secretion was more effective on IL-4 than IFN-, and that therefore the immune responses developed a tendency to a Th1-type reaction, although the effects were not very strong (Fig.…”
Section: Ova (µM)mentioning
confidence: 99%
“…Some reports have indicated that the exposure of mice to BPA affected their antigen-specific immune responses. Tian 21) suggested that the production of Th2-type cytokines y To whom correspondence should be addressed. Fax: +81-29-838-8055; E-mail: yuko@affrc.go.jp Abbreviations: APCs, antigen presenting cells; BPA, bisphenol A; DMSO, dimethyl sulfoxide; ELISA, enzyme-linked immunosorbent assay; IL, interleukin; IFN, interferon; mAb, monoclonal antibody; XEs, xenoestrogens markedly increased in Trichinella spiralis infected mice inoculated orally with BPA.…”
mentioning
confidence: 99%
“…The authors inferred that BPA does not selectively activate the Th1 or Th2 path. BPA also enhances Th1 or Th2 response in vivo, depending on the doses [74,77]. In addition, prenatal exposure to BPA was shown to augment both Th1 and Th2 responses in adulthood [74].…”
Section: Other Miscellaneous Efectsmentioning
confidence: 97%
“…Genomic DNA was digested and removed using an RNase-Free DNase Kit (Qiagen). First strand cDNA was synthesized using oligo (dT) [12][13][14][15][16][17][18] primer (Invitrogen, Carlsbad, CA, USA) and the Omniscript RT Kit (Qiagen). The synthesized cDNA was thermocycled for PCR amplification with 1 mM each primer and 1.5 U of Taq polymerase.…”
Section: Generation Of Immature Dcs and Their Induction Of Maturationmentioning
confidence: 99%
“…[14][15][16] BPA was reported to enhance IL-4 production by T helper (Th) 2 cells in vitro while also enhancing the Th2 and Th1 immune responses, depending on the doses of BPA administered in vivo. 17,18 These experimental studies have indicated that BPA may help trigger allergic responses. However, the precise mechanism by which BPA regulates the Th responses has remained elusive.…”
Section: Introductionmentioning
confidence: 99%